Equilibrium and Kinetic Studies of Adsorption of Aqueous Crystal Violet by Peanut Shells - Begum, Hosne Ara; Islam, Md Ariful; Muslim, Tanvir (Bangladesh Pharmaceutical Journal, 2015)
In the present study, the ability of a non-conventional biosorbent, peanut shells (PnS) for the removal of crystal violet (CV), a cationic dye, from aqueous solution was evaluated. The surface zero point charge (pHzpc) of peanut shells was estimated and found to be 6.27. Batch adsorption experiments were performed and system variables were investigated including contact time, initial dye concentration, temperature and pH of the solution. The estimated equilibrium time was found to be 4 hours. The adsorption of CV on PnS was found to increase with the increment of initial concentration of CV solution and pH of the medium. The equilibrium adsorption data were fitted to the Langmuir and Freunlich isotherms. The best result was achieved with Langmuir isotherm model. The adsorption rates were found to be consistent with a pseudo-second-order model. The result showed that the amount of CV adsorbed decreased with the increase of temperature. It suggested that the adsorption occurred due to physical interaction and it was favorable at lower temperature. The value of activation energy Ea (11.27 kJ mol?1) revealed that adsorption process was spontaneous and exothermic in nature. The adsorption of crystal violet by peanut shell suggests that this adsorbent may be evaluated for removal of other dyes produced and/or used in pharmaceutical process industries. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22335 Bangladesh Pharmaceutical Journal 17(2): 163-171, 2014